Comparative Advantages of Jute Export in Bangladesh, China and India (Research in Agriculture Livestock and Fisheries, 2020)
The aim of this study was to review the trend of production and export of jute as well as comparative advantages of jute export of Bangladesh, China and India. In the case of production, India is the leading country which is followed by Bangladesh, China, Nepal, Zimbabwe, Uzbekistan, Egypt and others. However, Bangladesh plays the supreme role over other countries in the world for exporting jute. Jute export fluctuated erratically over the past four decades in these three most jute exporting countries. The Revealed Comparative Advantage (RCA) has been enumerated for comparing the jute export advantages in the global market. Bangladesh always enjoys greater comparative advantages than China and India although the revealed comparative advantages are less in recent years than those were one decade ago. But it can’t catch the high-value market because exporters have mainly focused on raw jute while jute goods have high potentiality. The recommended issues urge to enhance the productivity of jute cultivation, inaugurate more diversified products, and explore new markets for exports.Res. Agric., Livest. Fish.7(2): 183-190,  August 2020